Smart-Coating Corrosion Inhibitor for Carbon Steel Using LDH Modified with Laundry Detergent Waste - Irmayanti, Dwi; Jamilah, Badrotul; Agustin, Ardianti Dwi; Fitria, Maulida Rizki; Wijayanto, Herry (EduChemia: Jurnal Kimia dan Pendidikan, 2025)
This research was conducted with the aim of reducing environmentally harmful detergent waste while utilizing its anionic surfactant content for the development of Zn-Al LDH composites with benzimidazole as a smart corrosion inhibitor for low-carbon steel, providing dual protection. The samples used in this research included detergent waste collected from commercial laundry services in the Ketintang area of Surabaya, commercial detergent, dodecylbenzenesulfonate, and pure Zn-Al LDH. The methodology involves the synthesis of Zn-Al LDH followed by characterization using FTIR, XRD, and TGA. The results indicate that the thermal decomposition profiles of Zn-Al LDH intercalated with commercial detergent, detergent waste, and dodecylbenzenesulfonate confirm that Zn-Al LDH can be modified with laundry waste. Additionally, interactions between Zn-Al LDH and benzimidazole enhance the crystalline structure of Zn-Al LDH, improving its quality as an anticorrosion material. Quantitative corrosion rate analysis using the weight loss method revealed that the Zn-Al LDH–dodecylbenzenesulfonate–benzimidazole sample exhibited the highest corrosion resistance, followed by the Zn-Al LDH–commercial detergent–benzimidazole, Zn-Al LDH–pure–benzimidazole, and Zn-Al LDH–detergent waste–benzimidazole samples. Overall, these findings support the feasibility of repurposing detergent waste as a functional additive for Zn-Al LDH-based corrosion inhibitors. Although not as effective as pure commercial surfactants, detergent waste provides environmental and functional benefits, reducing environmentally harmful and sustainable smart coatings for corrosion protection.